Internet addiction and anxiety in asthmatic children after the first year of the COVID-19 pandemic - Pınar Gökmirza Özdemir; Velat Çelik; Burçin Beken; Özge Türkyılmaz Uçar; Sibel Kaplan; Mehtap Yazıcıoğlu (Trends in Pediatrics)
Objective: Studies have revealed that people with asthma have a higher risk of anxiety during the COVID-19 pandemic. The relationship between internet addiction and anxiety has long been known, but to our knowledge, no studies have combined anxiety in asthmatic children and adolescents with internet use. This study investigated the relationship between anxiety levels and internet use in asthmatic children and adolescents during the late stage of the COVID-19 pandemic.